PROSPEK DAN TANTANGAN PETANI KELAPA SAWIT SWADAYA DI DESA AIR HITAM KECAMATAN UKUI KABUPATEN PELALAWAN DALAM MENGHADAPI SERTIFIKASI ISPO - Sibarani, Dewi Yosefin Tumiar; Hutabarat, Sakti; Dewi, Novia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Increasing demand for palm oil and palm oil derivative products has triggered demand for oil palm fruit. This phenomena has been responded by Indonesian oil palm growers by increasing oil palm production through land expansi on. Land expansion has been claimed as the source of deforestation, land degradation, biodiversity loss, greenhouse gas emission, and land conflicts. The Indonesian Sustainable Palm Oil has been established to promote sustainable oil palm production. However, the implementation of the certification program face various problem, especially at the smallholder levels. The objective of this study is to analyze the performance of independent oil palm smallholders, to assess the application of good agricultural practices in relation with the ISPO standards and to analyses prospects and chalenges toward certification ISPO. The study use agribusiness income analyses, scaling method to measure the smallholders practices based on the ISPO standard and descriptive method to analyze prospects and chalenges faced by smallholders to obtain ISPO certification. The result shows that the oil palm smallholder profits on average are above the regional wage standard. However, the smallholders compliance to the ISPO standards is only 43.5%. Certification ISPO would promote better acces to independent smalholder in market acces, financial acces and endorse sustainable production of oil palm. However, independent oil palm smallholers face various chalenges to obtain certificate of ISPO.  This figure shows that there will be lots of effort to be done to get the ISPO certification. Keywords : Oil palm, ISPO certification, smallholders’ performance, independent smallholders